The dual function of microglial polarization and its treatment targets in ischemic stroke - Mo, Yong; Xu, Weilin; Fu, Kaijing; Chen, Hainan; Wen, Jing; Huang, Qianrong; Guo, Fangzhou; Mo, Ligen; Yan, Jun (Frontiers in Neurology, 2022)
Stroke is the leading cause of disability and death worldwide, with ischemic stroke occurring in 5% of the global population every year. Recently, many studies have been conducted on the inflammatory response after stroke. Microglial/macrophage polarization has a dual function and is critical to the pathology of ischemic stroke. Microglial/macrophage activation is important in reducing neuronal apoptosis, enhancing neurogenesis, and promoting functional recovery after ischemic stroke. In this review, we investigate the physiological characteristics and functions of microglia in the brain, the activation and phenotypic polarization of microglia and macrophages after stroke, the signaling mechanisms of polarization states, and the contribution of microglia to brain pathology and repair. We summarize recent advances in stroke-related microglia research, highlighting breakthroughs in therapeutic strategies for microglial responses after stroke, thereby providing new ideas for the treatment of ischemic stroke.